Investigating the digital divide in a rural community in the Philippines - Talandron, Marie May P. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2016)
Digital divide is a global social issue that deals with the inequality of availability, access, and utilization of Information and Communications Technology (ICT). This study investigated the incidence of the digital divide and its factors among the residents in a rural community in the Philippines. A survey based on the concepts of measurement of Digital Divide on a micro level was conducted to identify factors based on ICT Development Index (IDI), Digital Access Index (DAI), and Digital Opportunity Index (DOI). It was found that majority of the respondents were "non-users" of ICT due to lack of knowledge, access, and comfort in doing so. Therefore, a digital divide exists and the factors that cause the gap are age, employment status, educational attainment, and household income.